Comparison of popliteal anesthesia and spinal anesthesia in patients with the diabetic foot: Our clinical series (Annals of Medical Research, 2021)
Aim: Surgery is of great importance in the treatment of diabetic foot. We aimed to compare unilateral spinal anesthesia and ultrasound-guided popliteal block procedures in patients diagnosed with a diabetic foot ulcer.Materials and Methods: In this study, we included 54 patients diagnosed with diabetic foot ulcers in our hospital between September 2010 and December 2012. The patients were randomly divided into two groups of 27 patients each: Group I (Spinal group) and Group II (Popliteal group). Spinal anesthesia was performed in Group I, whereas ultrasound-guided popliteal block was performed in Group II. During and after the anesthesia, the total isotonic fluid given, average patient and surgeon satisfaction score, and length of hospital stay were evaluated.Results: In Group I, the average length of hospital stay was 6.07 ± 1.2 days, the total isotonic fluid given was 1832.2 ± 280.7 ml, and the average patient and surgeon satisfaction score was 2.44 ± 0.5. In Group II, the average length of hospital stay was 6.5 ± 1.04 days, the total isotonic fluid given was 731.11 ± 130.2 ml, and the average patient and surgeon satisfaction score were 3. In addition, in Group I, 9 patients had bradycardia and 12 patients had hypotension and nausea. The findings of the study indicate a statistically significant difference in terms of the total isotonic fluid given and average patient and surgeon satisfaction scores (p < 0.05). However, no statistically significant difference was observed in terms of hospital stay (p > 0.05).Conclusion: In conclusion, we believe that ultrasound-guided popliteal block provides more reliable and efficient analgesia than spinal anesthesia in patients with diabetic foot ulcers